THE ENTRY OF THE CENTRAL ASIAN RAILWAY INTO THE BUKHARA EMIRATE AND THE ACTIVITIES OF RAILWAY STATIONS - Ochildiyev F. B. (TARIXIY TADQIQOTLAR, 2025)
The article examines the construction of the Central Asian Railway and its entry into the territory of the Bukhara Emirate, stations on the Bukhara section of the railway and their activities. The number of passengers transported through the railway stations of the emirate, the amount of cargo sent to Russia on high-speed and slow trains from the stations, the amount of cargo arriving from Russia at the stations of the Bukhara section, as well as the income of the stations from the transportation of passengers and cargo were also analyzed.